Leaves to Lifestyle: Raising Awareness of Responsible Production Through Eco-Print Training in Yosowilangun, Gresik - Laily, Nur; Yahya, Yahya; Baihaqy, Ahmad; Zuhroh, Nur Fatimatuz; Satria, Vinza Hedi (OJS Universitas Muhammadiyah Gresik, 2025)
The dimension of Responsible Consumption and Production encompasses the conscientious manufacturing process of a product, with a focus on minimizing waste and residues that may pose environmental risks. Strategically situated within an industrial region, Gresik plays a pivotal role in advancing Sustainable Development Goal 12: Responsible Consumption and Production. This research endeavors to achieve a dual objective. Firstly, it aims to raise awareness about the significance of responsible production in Yosowilangun, Gresik, one of the busiest villages in the area. Additionally, the research seeks to economically empower women residing in this village. The Eco-Print fabrication employed in this study goes beyond utilizing random waste materials; instead, it leverages the recycling of dried leaves waste, a readily available resource in Gresik. Acknowledging certain limitations, such as the scale of prototype production and the ongoing nature of the study due to the gradual nature of awareness-raising efforts, this research introduces a novel aspect by uniquely applying recycled leaf waste in textile production. This approach, not extensively explored in the industry, opens a new avenue for sustainable manufacturing and women's empowerment in developing regions. The product resulting from this research is not only environmentally friendly but also holds the potential to improve the socio-economic well-being of women in Yosowilangun Village.